Pregabalin for the treatment of generalized anxiety disorder: an update - Baldwin DS (Dove Medical Press, 2013)
David S Baldwin,1–3 Khalil Ajel,3 Vasilios G Masdrakis,4 Magda Nowak,1 Rizwan Rafiq31Clinical and Experimental Sciences Academic Unit, Faculty of Medicine, University of Southampton, Southampton, UK; 2Department of Psychiatry and Mental Health, University of Cape Town, Cape Town, South Africa; 3Southern Health NHS Foundation Trust, Southampton, UK; 4First Department of Psychiatry, Eginition Hospital, Athens University Medical School, Athens, GreeceAbstract: A previous review summarized what was then known about the potential role of pregabalin in the treatment of patients with generalized anxiety disorder (GAD): this review provides an update on its pharmacological properties and presumed mechanism of action, the liability for abuse, and efficacy and tolerability in patients with GAD. Pregabalin has a similar molecular structure to the inhibitory neurotransmitter gamma amino butyric acid (GABA) but its mechanism of action does not appear to be mediated through effects on GABA. Instead, its anxiolytic effects may arise through high-affinity binding to the alpha-2-delta sub-unit of the P/Q type voltage-gated calcium channel in “over-excited” presynaptic neurons, thereby reducing the release of excitatory neurotransmitters such as glutamate. The findings of randomized controlled trials and meta-analyses together indicate that pregabalin is efficacious in both acute treatment and relapse prevention in GAD, with some evidence of an early onset of effect, and broad efficacy in reducing the severity of psychological and physical symptoms of anxiety. It also has efficacy as an augmenting agent after non-response to antidepressant treatment in GAD. Continuing vigilance is needed in assessing its potential abuse liability but the tolerability profile of pregabalin may confer some advantages over other pharmacological treatments in the short term for treatment in patients with GAD.Keywords: generalized anxiety disorder, efficacy, tolerability, pregabalin